Improving rapid multiplication of sweetpotato (Ipomoea batatas L. (Lam)) pre-basic seed using sandponics technology in East Africa - Wanjala, Bramwel W.; Rajendran, S.; Makokha, P.; Ssali, R.T.; McEwan, M.; Kreuze, Jan F.; Low, Jan W. (Cambridge University Press, 2020)
Sweetpotato (Ipomoea batatas, Convolvulaceae) is an important food crop in Sub-Saharan Africa (SSA). Lack of access to quality sweetpotato planting material after sweetpotato limits utilization of market oriented improved clones and new varieties. Obtaining clean planting material in the right quantity and quality is a challenge in the SSA region. Farmers often obtain planting materials from their own sources with multiple rooting, drawn from a previous crop or neighbors and face the risk of it being infected with sweetpotato viruses. The objective of this study was to examine the economic and physical yield performance of sandponics multiplication method by comparing with conventional soil method using optimal N-nutrient inputs. The performance of five sweetpotato cultivars (Irene, Delvia, Tanzania, Gweri, and Kabode) in the modified prototype sweetpotato nutrient media was evaluated. Vine production utilizing modified sandponics nutrient media with trellised plants was compared to the conventionally used soil media. Analysis of variance indicated that the main effects of cultivar and substrate were highly significant (p < 0.0001) for nodes produced, vine multiplication rate (VMR), number of cuttings produced, and vine length. In addition, cultivar by substrate interaction was highly significant at 0.01 probability level for nodes produced, VMR, and vine length. Vine multiplication rate was 33% higher in the sandponics system compared to the conventional soil method of multiplying sweetpotato vines. Among the cultivars studied, Irene was the most favorable cultivar with a VMR of 65.2 in sand and 45.5 in soil. The cost-effectiveness analysis indicates that the cost per cutting (i.e., 3–4 nodes) produced from sandponics method was 4.6 KSH (US$ 0.046) as compared to 3.1 KSH (US$ 0.031) per cutting produced from conventional method. Sandponics system is competitive due to its capability of increased VMRs. However, the optimal number of ratooning needs to be investigated to understand the economies of scale in future research.